Network pharmacology and molecular docking analysis on molecular targets and mechanisms of scar healing ointment in the treatment of hypertrophic scars - Jiang, Lijuan; Zeng, Xiandong; Li, Hongjun; Wu, Jingping (Frontiers in Pharmacology, 2025)
IntroductionHypertrophic scars (HSs) are characterized by complex mechanisms and impose substantial economic and psychological burdens on patients with wounds. Recent studies have reported that various extracts from traditional Chinese medicines can help prevent and treat HSs. Scar healing ointment (SHO), a modified traditional Chinese prescription applied externally, has demonstrated potential in the clinical treatment of HSs, though its underlying mechanisms remain unexplored.MethodsIn this study, we systematically identified the active ingredients of the SHO formula and their potential targets using multiple databases (TCMSP, HERB, UniProt, GeneCards, DisGeNet, OMIM, PharmGKB, TTD) and explored the possible underlying mechanisms by which SHO treats HSs using bioinformatic analyses, including protein-protein interaction (PPI) network analysis, GO and KEGG enrichment analyses, and molecular docking.ResultsOur results indicated that the primary active ingredients in the SHO formula include quercetin, beta-sitosterol, kaempferol, stigmasterol, luteolin, alloimperatorin, acacetin, and (E)-2,3-bis(7-methoxy-2-oxochromen-8-yl)prop-2-enal. Protein-protein interaction network analysis revealed that the hub target proteins of the SHO formula are AKT1, MAPK1, CCND1, TP53, GSK3B, BCL2, CDKN1A, ESR1, and MYC. GO and KEGG enrichment analyses showed that these hub target genes are involved in processes and pathways related to apoptosis and responses to oxidants. Molecular docking analysis demonstrated that the MAPK1-stigmasterol and ESR1-alloimperatorin complexes exhibited strong binding affinities (–5.31 and –6.09) and formed multiple hydrogen bonds (3 and 2, respectively).DiscussionThese findings suggest that SHO may exert its effects by modulating MAPK1 and ESR1 proteins, thereby contributing to the prevention and treatment of HSs. This study offers new drugs and target candidates for the prevention and treatment of HSs and provides theoretical support for further research and application of the SHO formula. Nevertheless, additional in vivo and in vitro studies are necessary to validate these mechanisms.